h+2(h-6)=18

Simple and best practice solution for h+2(h-6)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+2(h-6)=18 equation:


Simplifying
h + 2(h + -6) = 18

Reorder the terms:
h + 2(-6 + h) = 18
h + (-6 * 2 + h * 2) = 18
h + (-12 + 2h) = 18

Reorder the terms:
-12 + h + 2h = 18

Combine like terms: h + 2h = 3h
-12 + 3h = 18

Solving
-12 + 3h = 18

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3h = 18 + 12

Combine like terms: -12 + 12 = 0
0 + 3h = 18 + 12
3h = 18 + 12

Combine like terms: 18 + 12 = 30
3h = 30

Divide each side by '3'.
h = 10

Simplifying
h = 10

See similar equations:

| 10x+4y+5z=170 | | 4(x+3)=6(2x-5) | | -7/4c=-7 | | F(7)-f(4)/7-4 | | -18=2/3x | | 3(x+7)=6(-3+7x) | | -5/6d=5 | | (1.6x^3+4.9x^2-3.7x)-(-4.1x^3-4.8x^2+95)= | | Q=t/12 | | 0.5a-3=7-3/4a | | 5(2x-2)=5(x-1) | | 7u+5+18u+18=248 | | -7(2x-5)+5(3x-5)-2=6-9 | | 21+1.5h=10+2.75h | | (-1/6x^6)(-1/5x) | | -7(2x-5)+(3x-5)=6-9 | | 90=18y+30-5y-5 | | -2(3y-3)-y=-3(y-2) | | 5+c=8 | | 3=-3(11-s)/7 | | .3(8)+x=.5(8+x) | | 6y-14(-2y+8)=432 | | D=4m+9 | | 2.5+5.75=2+3.75a | | 4y=16-8x | | 3(2x-4)=32-5(x-2) | | 156=18x+21+8x+5 | | 2(3x+4)=-5(5x-3) | | -19-5x=-17x+17 | | 17x+x=-4x | | 7x-7=13+12y | | 17r+18=221-12r |

Equations solver categories